Identification and In Vivo Functional Characterization of Novel Compound Heterozygous BMP1 Variants in Osteogenesis Imperfecta. Issue 2 (February 2015) - Cho, Sung Yoon; Asharani, P.V.; Kim, Ok‐Hwa; Iida, Aritoshi; Miyake, Noriko; Matsumoto, Naomichi; Nishimura, Gen; Ki, Chang‐Seok; Hong, Geehay; Kim, Su Jin; Sohn, Young Bae; Park, Sung Won; et al.
<x xml:space="preserve">Abstract</x> Skeletal survey and novel BMP1 variants (c.808A>G, c.1297G>T) in a Korean patient with OI who had an umbilical hernia, frequent fractures, a markedly short stature, delayed motor development, scoliosis, and dislocation of the radial head, with a bowed radius and ulna. The former variant caused a missense change p.(Met270Val) and the latter variant caused the skipping of exon 10. The hypofunctional nature of the two variants was demonstrated in a zebrafish assay. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>